2018
DOI: 10.1016/j.celrep.2018.03.102
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell RNA-Seq Reveals Transcriptional Heterogeneity in Latent and Reactivated HIV-Infected Cells

Abstract: Despite effective treatment, HIV can persist in latent reservoirs, which represent a major obstacle toward HIV eradication. Targeting and reactivating latent cells is challenging due to the heterogeneous nature of HIV-infected cells. Here, we used a primary model of HIV latency and single-cell RNA sequencing to characterize transcriptional heterogeneity during HIV latency and reactivation. Our analysis identified transcriptional programs leading to successful reactivation of HIV expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
105
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(110 citation statements)
references
References 52 publications
3
105
0
Order By: Relevance
“…Furthermore, these investigators identified a transcriptional signature that distinguished these clusters. This signature contains some of the same genes we observe as being associated with HIV gene expressing in our study, such as IL-32, GAPDH, HLA-E, and CD96, but also many different genes (Golumbeanu et al, 2018). …”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Furthermore, these investigators identified a transcriptional signature that distinguished these clusters. This signature contains some of the same genes we observe as being associated with HIV gene expressing in our study, such as IL-32, GAPDH, HLA-E, and CD96, but also many different genes (Golumbeanu et al, 2018). …”
Section: Discussionmentioning
confidence: 57%
“…; Bolton et al, 2017; Martrus et al, 2016). Two recent publications have also examined HIV latency using scRNA-seq of a primary cell model (Golumbeanu et al, 2018) and from sorted patient samples (Cohn et al, 2018), yielding important insights. In particular, Golumbeanu et al (2018) observed two clusters of cells in a primary cell model system that exhibited distinct transcriptional phenotypes, associated with different levels of viral gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…6C). infected human primary CD4+ T cells [11,16,81,82]. scRNA-Seq, however, has been technically challenging, requiring single cell isolation, RNA amplification and complex data analysis.…”
Section: High Transcriptional Variability Of Individual Vdnas In the mentioning
confidence: 99%
“…Single cell RNA-seq technology is transforming the study of cellular heterogeneity 1,2 , differentiation 3,4 , and cellular response to stress and stimulation 5,6,7 . Gene expression levels in tens of thousands of single cells are now routinely measured in a single scRNA-seq experiment 8 and more scRNA-seq datasets are becoming available each day.…”
Section: Introductionmentioning
confidence: 99%